How to make appointments by telephone - Pease, Allan (Sydney : Pease Training [production company] ; Sydney : First Training [distributor], 1990)
3 sets of kits that described on communication skills by telephone. Explain step by step to answer and make an appointments by telephone
Keywords: Telephone etiquette; Telephone in business; Business communication